Effectiveness of a virtual role-play environment as a preparation activity for story writing - Robertson, Judy (The University of Edinburgh: College of Science and Engineering: The School of Informatics, 2000)
Improvisational dramatic role-play activities are used in classrooms to encourage children to explore the feelings of the characters in a story. Roleplay exercises can give a story personal significance to each child, and an insight and understanding of the characters which is reflected in stories written afterwards. The thesis describes the development of a virtual environment designed for similar dramatic role-play exercises. The thesis then investigates its effectiveness as a preparation activity for writing stories. It examines the effects the virtual role-play environment has on the characterisation in children’s imaginative writing. It also investigates the social interactions which children engage in and the moral decisions they make during the role-play; and the motivational effects of the virtual roleplay environment. The virtual role-play environment is based on a commercial computer game. Two children and one role-play leader interact with each other in a perceptually realistic virtual world. Each role-player controls an avatar in order to move around this graphical world, and improvise by sending and receiving typed messages. The high quality graphics, sounds and music contribute to the users’ feelings of perceptual presence while the communication between role-players promotes feelings of social presence. The role-players’ emotional engagement with the other characters and the conflict within the adventure encourages them to experience self presence. The virtual role-play environment was evaluated in a field study with sixty children aged between ten and twelve years. The characterisation in stories written after using the virtual role-play environment was compared to the characterisation in stories written under normal classroom circumstances. The stories were compared using a new, fine-grained analysis scheme for assessing children’s writing. The main result is that the stories written after the virtual role-play contained more dialogue and more indications of relationships between the characters than normal classroom stories. Analysis of the typed communication exchanged between the role-players during the game shows that the role-players formed relationships with the other characters. They also made judgements about the characters’ personalities and to a lesser extent expressed emotional involvement during the game. They made moral decisions and could back up their decisions with reasons. Expert evaluation supports the view that the virtual role-play environment is particularly beneficial to children with low literacy standards. Finally, it also benefits children with low literacy motivation and little interest in school work.
The effectiveness of a virtual role-play environment as a preparation activity for story writing
Institute for Communicating and Collaborative Systems
Keywords: Roleplay; Story Writing